A Rare Presentation of Pellet Injury in the Neck. (5th May 2011) - Gupta, Bulbul; Gulati, Achal; Gupta, Divya
Abstract : Penetrating neck injuries are dangerous and deserve emergency treatment by virtue of the vital structures present underneath. There is a potential risk of unrecognized vascular injury and retained foreign bodies with their associated complications in these wounds. Therefore, an early diagnostic workup to localize the site of injury and an immediate neck exploration are important.